2014
DOI: 10.1182/blood-2013-08-521518
|View full text |Cite
|
Sign up to set email alerts
|

SET-NUP214 is a recurrent γδ lineage-specific fusion transcript associated with corticosteroid/chemotherapy resistance in adult T-ALL

Abstract: Key Points SET-NUP214 is a recurrent (6%) γδ lineage-specific fusion transcript in adult T-ALL. SET-NUP214 is strongly associated with corticosteroid and chemotherapy resistance but does not negatively influence clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 23 publications
5
56
0
Order By: Relevance
“…SET-NUP214 was first detected in a patient with acute undifferentiated leukemia (AUL) (1), and later detected in two patients with acute myeloid leukemia (AML) (2,5). Recent increasing evidence supports an association between SET-NUP214 and pediatric and adult T-cell acute lymphoblastic leukemia (T-ALL) with a frequency of ~3.3-10.3% (3,4,(6)(7)(8)(9)(10)(11)(12). Gorello et al (4) reported an estimated incidence of SET-NUP214 in adult T-ALL patients of 4.6% (7/152 cases) (4).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…SET-NUP214 was first detected in a patient with acute undifferentiated leukemia (AUL) (1), and later detected in two patients with acute myeloid leukemia (AML) (2,5). Recent increasing evidence supports an association between SET-NUP214 and pediatric and adult T-cell acute lymphoblastic leukemia (T-ALL) with a frequency of ~3.3-10.3% (3,4,(6)(7)(8)(9)(10)(11)(12). Gorello et al (4) reported an estimated incidence of SET-NUP214 in adult T-ALL patients of 4.6% (7/152 cases) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Gorello et al (4) reported an estimated incidence of SET-NUP214 in adult T-ALL patients of 4.6% (7/152 cases) (4). The current typical treatment for T-ALL patients with SET-NUP214 is allogeneic hematopoietic stem cell transplantation (allo-HSCT), as chemotherapy resistance is common (12). The 3-year overall survival (OS) rate was reported to be 73% in 9 patients who received allo-HSCT (12).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations